PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROSENTASE KEPEMILIKAN MANAJEMEN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Ramadhani, Laras Surya; Hadiprajitno, Basuki (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
The aim of this research is to analyze the influence of corporate social responsibility to firm value and theinfluence of percentage of management ownership as the moderating variable in relations betweencorporate social responsibility and firm value. The samples of this research are the manufacturing firmslisted in Indonesian Stock Exchange in 2010 and 2011. The samples are collected using purposivesampling method and result 74 firms fulfilling criterion as this research sample. Data analyzed by classicassumption tests and examination hypothesis by multiple linier regression method. The result of thisresearch show that simultaneously the effect of corporate social responsibility, percentage of managementownership and its interaction was significant, but partially only interaction between Corporate SocialResponsibility and percentage of management ownership have an effect as moderating variable thatstrengthen relationship between corporate social responsibility and firm value.Keywords:corporate social responsibility, management ownership, firm value